Transcriptomic Analysis of Resistant and Susceptible Bombyx mori Strains Following BmNPV Infection Provides Insights into the Antiviral Mechanisms. (18th April 2016) - Li, Gang; Qian, Heying; Luo, Xufang; Xu, Pingzhen; Yang, Jianhua; Liu, Mingzhu; Xu, Anying
Abstract : Purpose . To decipher transcriptomic changes and related genes with potential functions against Bombyx mori nucleopolyhedrovirus infection and to increase the understanding of the enhanced virus resistance of silkworm on the transcriptomic level. Methods . We assembled and annotated transcriptomes of the Qiufeng (susceptible to infection) and QiufengN (resistant to infection) strains and performed comparative analysis in order to decipher transcriptomic changes and related genes with potential functions against BmNPV infection. Results . A total of 78, 408 SNPs were identified in the Qiufeng strain of silkworm and 56, 786 SNPs were identified in QiufengN strain. Besides, novel AS events were found in these 2 strains. In addition, 1, 728 DEGs were identified in the QiufengN strain compared with Qiufeng strain. These DEGs were involved in GO terms related to membrane, metabolism, binding and catalytic activity, cellular processes, and organismal systems. The highest levels of gene representation were found in oxidative phosphorylation, phagosome, TCA cycle, arginine and proline metabolism, and pyruvate metabolism. Additionally, COG analysis indicated that DEGs were involved in "amino acid transport and metabolism" and "carbohydrate transport and metabolism." Conclusion . We identified a series of major pathological changes in silkworm following infection and several functions were related to the antiviral mechanisms of silkworm.